Профессор Харьковского университета Евгений Георгиевич Кагаров - Кадеев, В. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
Kadeev V.I. Professor of the Kharkov State University Eugeniy Georgievitch Kagarov